De novo loss of function mutations in KIAA2022 are associated with epilepsy and neurodevelopmental delay in females. Issue 5 (29th September 2016) - Webster, R.; Cho, M.T.; Retterer, K.; Millan, F.; Nowak, C.; Douglas, J.; Ahmad, A.; Raymond, G.V.; Johnson, M.R.; Pujol, A.; Begtrup, A.; McKnight, D.; et al.
Abstract :